A Case Study On Improving Business To Business Warranty Returns Warehouse Dock To Receipt Throughput Time In Sustaining Customers Satisfaction - Lee, Kok Peng (2014)
Leading manufacturers in various industries are focusing on improving the reverse logistics process in order to recapture revenue and retain customers. Warranty returns plays a vital role in the entire supply chain network. It delivers value by enhancing higher levels of customer loyalty & retention. The management project case study takes a vertical look at reverse logistics, examining the warranty returns challenges faced by the reverse logistics division in a well-known semiconductor corporation.